2020
DOI: 10.1371/journal.pcbi.1007820
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based and continuous models of hopper bands for the Australian plague locust: How resource consumption mediates pulse formation and geometry

Abstract: Locusts are significant agricultural pests. Under favorable environmental conditions flightless juveniles may aggregate into coherent, aligned swarms referred to as hopper bands. These bands are often observed as a propagating wave having a dense front with rapidly decreasing density in the wake. A tantalizing and common observation is that these fronts slow and steepen in the presence of green vegetation. This suggests the collective motion of the band is mediated by resource consumption. Our goal is to model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…For simplicity, the Topaz model focused on inter-locust interactions and ignored interactions between locusts and the environment. While there exists some continuum models of locust food interactions to investigate the effect of food on peak locust density [35] or to consider hopper band movement [36], we are not aware of any studies that consider locustlocust and locust-food interactions as well as gregarisation in a continuum setting.…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity, the Topaz model focused on inter-locust interactions and ignored interactions between locusts and the environment. While there exists some continuum models of locust food interactions to investigate the effect of food on peak locust density [35] or to consider hopper band movement [36], we are not aware of any studies that consider locustlocust and locust-food interactions as well as gregarisation in a continuum setting.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide literature demonstrating that coarse graining approaches can be used to derive DE models that approximate ABM dynamics [3,9,12,17,35,60,61]. Such DE models are advantageous because they are usually simple to solve (either analytically or numerically), interpretable, and provide insight into how changing ABM parameters can lead to emergent behaviours.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Previous ecological studies have demonstrated some of the advantages of both extensive simulation and model coarse graining for ABM analysis [16]. For example, Bernoff et al [17] model the foraging behaviour of the Australian plaque locust with a discrete and stochastic ABM. In the model, individual locusts forage and feed on a given resource (representative of food) and, in turn, create a spatial gradient of this resource.…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity the model focused on inter-locust interactions and ignored interactions between locusts and the environment. While there exists some continuum models of locust food interactions to investigate the effect of food on peak locust density [32] or to consider hopper band movement [33], we are not aware of any studies that consider locust-locust and locust-food interactions as well as gregarisation in a continuum setting. This paper is organised as follows: we begin with the derivation of a PDE model in which locusts only interact with food when they come into direct contact with it.…”
Section: The Non-local Aggregation Equation First Proposed By Mogilnmentioning
confidence: 99%